IMPROVING STUDENTS’ MATHEMATICAL UNDERSTANDING AND REASONING ABILITY AND MOTIVATION THROUGH THINK TALK WRITE APPROACH (TTW) JUNIOR HIGH SCHOOL STUDENTS - Diky Irawan; Euis Eti Rohaeti; Asep Ikin Sugandi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study aims to examine the achievement and improvement of the ability of understanding and mathematical reasoning and motivation through Think Talk Write (TTW) approach to junior high school students. The population in this study is all junior high school in West Bandung Regency and the sample is class VIII of SMPS Darun Nasya, The instrument used in the research is a question of understanding and mathematical reasoning and questionnaire of learning motivation attitude, then the data obtained is processed through a two-way ANOVA test and correlation and regression test, data processing using IBM Statistics SPSS 21. Results of research involving TTW as independent variables in the experimental class and direct learning in the control class showed: There was a difference in achievement and improvement of mathematical understanding between control and experiment class, There are differences in achievement and improvement of mathematical reasoning between control and experiment class, There is difference of student's learning motivation between control and experiment class.